(untitled) (Minerva, 2019)
The author of this article has tried to demonstrate that the last three verses of the Odyssey’s proem have been added later, at least after Christ’s birth, as it appears –besides other element– from the comparison between the Iliad’s and the Odyssey’s proems, as well as from the fact that neither Virgil nor Horace seem to have knowledge of them. Besides the author has shortly dwelt upon the proems of some of the most renowned epic poems of antiquity.